(untitled) (Ius Novum, 2026)
T he article analyses problems arising from the statutory regulation of reviews in the proceedings for the award of the postdoctoral degree of doktor habilitowany. The analysis covers: the substantive scope of the review; the nature of scientific achievements constituting a significant contribution to the development of the discipline of legal sciences; and the meanings of the terms ‘monograph’ and ‘series of thematically related scientific articles’. The structure of the review and its basic components are also presented: the introduction; the analysis and evaluation, including formal and substantive assessment (of the choice of topic, the structure of the study, the research problem, research objective, research thesis, and research hypothesis, the appropriateness of the research methods applied, and the significant contribution to the development of the discipline of legal sciences); as well as the quality of the review, its form, and the deadline for its preparation.